2023
DOI: 10.3390/healthcare11142099
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Nursing Faculty Job and Career Satisfaction, Turnover Intentions, and Professional Outlook: A National Survey

Abstract: Background: Retaining talented and experienced nurses in clinical practice and academia is crucial for maintaining continuity, ensuring high-quality care and education, and fostering a positive work environment. Although factors influencing nursing staff retention are well documented, little is known about how workplace factors impact nursing faculty retention outcomes. Methods: A national survey involving 645 nursing faculty across Canada was undertaken. Multivariate regression analysis with interaction effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…In a separate study conducted in China, clinical nurses who can adapt to the changes brought about by research are more likely to make practical problems solving efforts [ 19 ]. Research-friendly workplace environments are frequently associated with greater job satisfaction, according to a study of nursing faculty members working in Canadian colleges and universities [ 20 ]. However, a study from Cyprus found that the amount of research information can occasionally be overwhelming to nurses, making it difficult to uncover relevant and valuable findings for the patients who comprise their group [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a separate study conducted in China, clinical nurses who can adapt to the changes brought about by research are more likely to make practical problems solving efforts [ 19 ]. Research-friendly workplace environments are frequently associated with greater job satisfaction, according to a study of nursing faculty members working in Canadian colleges and universities [ 20 ]. However, a study from Cyprus found that the amount of research information can occasionally be overwhelming to nurses, making it difficult to uncover relevant and valuable findings for the patients who comprise their group [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Job satisfaction in as one of the independent factors of nurses' retention and turnover intention. Moreover, the studies conducted by Boamah et al (2023) and Bocean, Popescu, Varzaru, Avram and Iancu (2023) also claimed that factors affecting job satisfaction and turnover intention change over time which depends on sociopolitical climate. Thus, the job satisfaction is high when employees are acknowledged for their hard work and rewarded on the accomplishment of the tasks (Bocean et al, 2023).…”
Section: Job Satisfactionmentioning
confidence: 99%
“…Job satisfaction is defined as "how people feel about their job" (Boamah, Kalu, Havaei, McMillan & Belita, 2023). The job satisfaction is a complex phenomenon with several mediating variables and predictors.…”
Section: Job Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it was demonstrated that a supportive workplace culture positively influenced professionals’ satisfaction and outlook, while negatively impacting the intention to leave the job. Conversely, work–life imbalance decreased satisfaction and outlook, while increasing turnover intention [ 31 ]. Job satisfaction is crucial to prevent burn-out.…”
Section: Introductionmentioning
confidence: 99%